2018
DOI: 10.1093/jpepsy/jsy063
|View full text |Cite
|
Sign up to set email alerts
|

Parent Training for Feeding Problems in Children With Autism Spectrum Disorder: Initial Randomized Trial

Abstract: This trial provides evidence for feasibility, satisfaction, and fidelity of implementation of PT-F for feeding problems in young children with ASD. Feeding outcomes also appeared favorable and lends support for conducting a larger efficacy trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…Given the pervasiveness, intensity, and duration of feeding problems in individuals with ASD, the need for preventative strategies and evidence-based treatments is clear. Johnson et al 21 recently piloted a parent training program for feeding problems in children with ASD ages 2 through 7 years of age. This randomized trial with wait list control was delivered in eleven 60-90 minute sessions over the course of 20 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the pervasiveness, intensity, and duration of feeding problems in individuals with ASD, the need for preventative strategies and evidence-based treatments is clear. Johnson et al 21 recently piloted a parent training program for feeding problems in children with ASD ages 2 through 7 years of age. This randomized trial with wait list control was delivered in eleven 60-90 minute sessions over the course of 20 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding and disruptive behaviors were significantly reduced and both food selectivity and mealtime behavior issues improved significantly relative to the control group. 21 Another study of a different feeding program reported improvements in parental self-efficacy, mealtime difficulty, and range of foods consumed after implementation of an educational intervention for parents of young children with ASD. 22 These and further research studies are needed to develop evidence-based guidelines and practical resource for parents and to help improve mealtime behavior issues and food selectivity before they exacerbate the health and social challenges that children with ASD already face.…”
Section: Discussionmentioning
confidence: 99%
“…Sankey [25] presented an overview of 3 parenting programs and their effectiveness. Johnson [26] studied the efficacy of a program delivered individually to improve feeding behaviors in children using behavior modification techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Psycho-education of ASD was the most common component found across studies. One study concentrated on establishing feeding routines in children [26] while another concentrated on improving sibling relationship among the children. One study concentrated on improving parental efficacy by using Mindfulness strategy [23] while another used psychological counseling [20] to help parents deal with the situation.…”
Section: Study Themesmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a neurological and developmental disease characterized by social interaction and communication disorders, limited interest in activities and stereotyped behaviors (Johnson et al, 2019). ASD includes autistic disorder (AD), Asperger's syndrome and other undefined common developmental disorders (Moore et al, 2012).…”
Section: Introductionmentioning
confidence: 99%